Analisis Kemampuan Menyimak Informasi dari Media Audio pada Siswa Kelas VI SD - Yaumi Aulia Fadira; Chandra Chandra; Inggria Kharisma (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Listening ability is one of the basic language skills that is important in supporting the learning process of students in elementary schools. However, in practice, students still have difficulty in capturing information from listening materials, especially when learning is carried out conventionally without the support of interesting media. This study aims to analyze the ability to listen to information from audio media in grade VI elementary school students with a qualitative approach using the case study method. The steps of the case study method are determining the focus of the study, literature, determining the case, data processing, data analysis, negotiating the results of the study, and conclusions. The subjects of the study consisted of five students who were analyzed based on their answers to five thematic audio media-based listening questions. The results of the study showed that students were able to understand the contents of the story, recognize characters and traits, and capture moral messages from the listening materials. However, there were still shortcomings in the aspect of regularity in reorganizing information and in-depth understanding of the character of the character. The novelty of this study lies in the analytical approach based on mapping student difficulties and the use of audio media that is relevant to everyday life, which has been proven to increase students' imagination and involvement in listening activities. This study recommends the use of audio media in a varied and contextual way in learning Indonesian in elementary schools.